Grassroots indigenous organisations: keys to the re-foundation of native self-government in Bolivia - María Fernanda Herrera Acuña (Revista d'Estudis Autonòmics i Federals, 2025)
In Bolivia, indigenous grassroots organisations have developed a historical journey for territorial restoration and the establishment of their autonomy. This qualitative, descriptive, multiple-case comparative study, carried out in two indigenous towns in Bolivia – Charagua (Chaco-Guarani) and San Pedro de Totora Marka (Altiplano-Aymara) –, gives an account of the process carried out by their respective grassroots organisations and their systematic struggle and orientation towards territorial recovery and the establishment of their own governments. Both communities began and completed their process of conversion to self-government on the same date and under the same procedures, although the results were dissimilar: Charagua accepted its conversion and Totora rejected it. The analysis reveals the multiple tensions, struggles and agreements of the original grassroots organisations as promoters and mediators of the achievement of – or resistance to – autonomy, thanks to the exploitation or undermining of the structures of identity and political and governmental opportunities. At the same time, these organisations are presented as the appropriate instruments for the connection between identity-territoriality and State power.